Sistem Portable Dashboard Berbasis Android untuk Mobil Listrik - Bambang Sumantri; Anggita Abimayu; Ni’am Tamami (Jurnal Rekayasa Elektrika, 2018)
In the development of an electric car, many things should be considered for making it an environmentally friendly vehicle and therefore it is suitable for public use, one of them is the dashboard system. A dashboard is an interface device that connects the driver with the electrical and mechanical systems of the vehicle. In this study a dashboard system was developed to display information about electrical aspects of electric cars. The dashboard system is packaged in an Android-based smartphone that is placed on the steering wheel of the car using Bluetooth transmission. The system that is made is portable and universal on all Android smartphones so that with this system the driver can monitor the electrical condition easily and conveniently. The parameters displayed are battery voltage and capacity, current consumption, BLDC motor rotational speed, motor temperature, battery temperature, car speed and energy consumption. This system creates a reading value for each parameter that corresponds to the ratio of the standardized measuring instrument with an average error of 0.38% for the voltage sensor, 1.06% for the current sensor, 1.21% and 2.98% for the temperature sensor, 0.07% for the speed sensor and the use of the coulomb counting method for reading the state of charge (SoC) value produces an average error of 1.57%. By comparing the value of energy consumption reading with a standard wattmeter, we obtained an average difference of 1.69%.